Choking under pressure in sensorimotor skills: Conscious processing or depleted attentional resources? - Gucciardi, Daniel; Dimmock, J. (Elsevier BV, 2008)
Objectives: This study examined and compared the conscious processing hypothesis and the attentional threshold hypothesis as explanations for choking under pressure.Design: A 23 (anxiety level putting condition) within group design was employed.Methods: Twenty experienced golfers with handicaps ranging from 0 to 12 putted using three explicitknowledge cues, three task-irrelevant knowledge cues, and a single swing thought cue under low and high anxiety to test these opposing hypotheses.Results: Irrespective of anxiety the data revealed that putting performance was generally better in the swing thought condition requiring the mobilisation of less cognitive resources. Under increased cognitive anxiety putting performance deteriorated in the explicit knowledge condition, whereas performance did not deteriorate in the task-irrelevant and swing thought conditions, providing support for the conscious processing hypothesis.Conclusions: These results suggest that the type and/or amount of conscious processing may influence the anxiety–performance relationship. Future research should combine qualitative and quantitative methods to gain a more complete understanding of this relationship.